2003
DOI: 10.1109/jstqe.2003.819504
|View full text |Cite
|
Sign up to set email alerts
|

The role of auger recombination in inas 1.3-μm quantum-dot lasers investigated using high hydrostatic pressure

Abstract: InAs quantum-dot (QD) lasers were investigated in the temperature range 20-300 K and under hydrostatic pressure in the range of 0-12 kbar at room temperature. The results indicate that Auger recombination is very important in 1.3-m QD lasers at room temperature and it is, therefore, the possible cause of the relatively low characteristic temperature observed, of 0 = 41 K. In the 980-nm QD lasers where 0 = 110-130 K, radiative recombination dominates. The laser emission photon energy las increases linearly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
73
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 28 publications
8
73
0
Order By: Relevance
“…However, there have been few reports on the temperature sensitivity of the device characteristics using cavity length analysis [3], [4]. A recent experiment [5] has identified carrier leakage out of the QD as an underlying cause for the observed low modal gain and the relatively high temperature sensitivity of self-assembled QD lasers operating near 1 m. Studies on longer wavelength QD lasers (near 1.3 m) indicate Auger recombination also plays a role in the device temperature sensitivity [6]. Carriers which are thermally excited into the wetting layers surrounding the QD, lead to gain saturation at values significantly lower than achievable if saturation occurs due to full population inversion in the dot states.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been few reports on the temperature sensitivity of the device characteristics using cavity length analysis [3], [4]. A recent experiment [5] has identified carrier leakage out of the QD as an underlying cause for the observed low modal gain and the relatively high temperature sensitivity of self-assembled QD lasers operating near 1 m. Studies on longer wavelength QD lasers (near 1.3 m) indicate Auger recombination also plays a role in the device temperature sensitivity [6]. Carriers which are thermally excited into the wetting layers surrounding the QD, lead to gain saturation at values significantly lower than achievable if saturation occurs due to full population inversion in the dot states.…”
Section: Introductionmentioning
confidence: 99%
“…Previous calculations have shown that the rate of Auger recombination decreases with pressure in quantum dots due to the decreased overlap of the electron and hole wavefunctions involved in the Auger process with increasing band gap. 16 The measured decrease in threshold current with pressure ͑band gap͒ is therefore consistent with nonradiative Auger recombination dominating the threshold current at room temperature.…”
mentioning
confidence: 57%
“…Since the carrier recombination processes have different band gap dependencies, this allows one to separate which process dominates at threshold. 16 In the devices studied here, the lasing energy increases by ϳ8.4 meV/ kbars ͑inset of Fig. 2͒.…”
mentioning
confidence: 82%
“…2, there is a clear decrease in the gradient at high current injection levels for sample C. Identical behavior was obtained using a pulsed current source, ruling out heating effects. It is possible that other nonradiative recombination processes such as Auger recombination [13], [14] might begin to become significant at these high current levels.…”
Section: Discussionmentioning
confidence: 99%